FACTORS EFFECTING EXERCISE BEHAVIORS OF PATIENTS WITH CORONARY ARTERY DISEASE POST PERCUTANEOUS CORONARY INTERVENTION - ศรภิรมย์, สัญพิชา; ทำนอง, ชวนพิศ (วารสารพยาบาลศาสตร์และสุขภาพ, 2012)
The purpose of this descriptive research  was tostudy the exercise behaviors and investigate factorseffecting exercise behaviors of patients with postpercutaneous coronary intervention. The data werecollected from 200 coronary artery disease patients afterreceiving percutaneous coronary intervention, who hadtreatment followed up at out patient department of QueenSirikit Heart Center of the Northeast, Khon KaenUniversity. The research instruments were the interviewsexercise behaviors and factors effecting exercisebehaviors. The interviews were approved for contentvalidity by five scholars and cronbachûs alpha coefficientwas used to test their reliabilities of the exercisebehaviors and factors effecting exercise behaviors (0.94and 0.86, respectively) Data analyses were conductedin terms of univariate descriptive analyses, pearsonproduct-moment correlation and multiple regressionanalysis. The study results were as follows:1. The exercise behaviors of coronary heartdisease patients post percutaneous coronary interventionwere classified in low level (X=2.24, SD=1.03).2. Personal factor, perceived self-efficacy, priorrelated behaviors, and interpersonal factor weresignificantly related to exercise behaviors, and accountedfor 31.4 percent of the variance of the exercisebehaviors.